Self-purification effect in CdTe:Gd crystals - Nikonyuk, E.S.; Shlyakhovyi, V.L.; Kovalets, M.O.; Kuchma, M.I.; Zakharuk, Z.I.; Savchuk, A.I.; Yuriychuk, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The temperature dependences (T = 80 – 420 K) of the concentration of charge carriers and the Hall mobility in undoped CdTe and CdTe:Gd single crystals grown by the Bridgman method are studied. It is found that the conductivity type of CdTe:Gd crystals changes with increase in the impurity concentration in the melt: n-conductivity at 5.10¹⁷ – 3.10¹⁸ cm⁻³ and p-conductivity at 3.10¹⁸ – 10¹⁹ cm⁻³. The concentrations and ionization energies of A₁ (EA₁ = 0.05 eV) and A₂ (EA₂ = 0.12-0.15 eV) acceptors are determined from the temperature dependences of the Hall coefficient and the mobility of carriers. A long-term thermal treatment of gadolinium-doped p-CdTe crystals in the range 663 – 713 K is accompanied by the “self-purification” of the material from A₂- acceptors and compensating donors. The Gd impurity at C₀ > 3.10¹⁸ cm⁻³ is shown to bring no new electrical active centers into the CdTe lattice, by reducing, at the same time, the background of residual impurities. It is suggested that Te precipitates and Te inclusions serve as sinks for the above defects.